Evaluasi Program Budidaya Aglaonema dalam Menumbuhkan Entrepreneurial Spirit dan Implikasinya terhadap Ketahanan Ekonomi (Studi di Kecamatan Godean Kab Sleman DIY) - Penggalih, Paksi Mei; Huda, Amalia Nurul; Saraswati, Yudhistira (Universitas Gadjah Mada, 2025)
ABSTRACTThe agricultural sector plays an important role and makes a significant contribution to Indonesia's Gross Domestic Product (GDP). One of the leading agricultural commodities that has great economic potential is Aglaonema. Seeing the great potential of this commodity, Department of Sleman Regency Agriculture, Food and Fisheries carried out an Extension Program for Aglaonema Cultivation in Godean District, Sleman Regency. The aim of this research is to evaluate the implementation of Bimtek in fostering the entrepreneurial spirit of community. The research method used was descriptive qualitative using the Context, Input, Process and Product (CIPP) evaluation model. This research was conducted in Godean District in June 2024 using a purposive location selection method, it was the place where the extension program was implemented. The data used was primary data and secondary data. The primary data collection technique was carried out by direct interviews with several key implementation informants and extension participants.The research results show that (i) context evaluation, the extension program is considered successful by the community because there are facilities and infrastructure that support the cultivation of Aglaonema, including a suitable climate, availability of water, fertilizer, planting media, and space for cultivation. This motivates people to cultivate and do Aglaonema business. (ii) For input evaluation, the extension program was considered successful by the community because the organizers provide the facilities needed by the community to start cultivating Aglaonema, including seeds and planting media. (iii) Regarding the evaluation process, the extension program is also considered successful by the community because it teaches direct practice on how to plant and do Aglaonema business by experts. (iv) For product evaluation, the extension program is also considered successful by the community because it is considered to increase public knowledge in cultivation and increase motivation to do business with Aglaonema plants.